The effect of purple tea extract activity on selected metabolic syndrome parameters in mice - Mwangi, Erastus S; Wandili, S. Awuor (Meru: Meru University of Science and Technology., 2022)
Metabolic syndrome (MetS) is a cluster of metabolic abnormalities. Prevalence of MetS is documented at 50% and 87.5% in Africa and Kenya respectively. It is managed by combining lifestyle modification and pharmacotherapy. Although Camellia sinensis TRFK306 has been proven to induce weight loss in mice and humans, its effect on metabolic syndrome is yet to be investigated. This study aimed to investigate the effect of Camellia sinensis TRFK306 extract on MetS induced Sprague Dawley male rats. A total of thirty-five, six-weeks-old rats were acclimatized for one (1) week and randomized into 5 groups (n=7). Metabolic syndrome was induced using high- fat fructose diet for eight (8) weeks. Post-hoc statistical analysis using Tukey$1 (Bs multiple comparison test was used to analyze the effect of freeze-dried extracts of Camellia Sinensis TRFK306 on various markers of metabolic syndrome. Random blood sugar levels revealed significant differences (p = <0.0001), for experimental animals. Oral glucose tolerance results were significant (p = <0.0001). Total serum triglyceride levels was significant (p = <0.0001). Mean serum HDL-C levels revealed significant differences between the normal control and negative control (p = 0.0009), the negative control and low dose test (p = 0.0023), the negative control and high dose test (p = 0.0025) and the negative control and positive control (p = 0.0014). The mean serum LDL-C levels revealed significant difference (p= <0.0001). Camellia Sinensis TRFK306 possessed significant beneficial effects on various markers of metabolic syndrome.s